Transcriptomic Profiles of Splenic CD19+ B Cells in Mice Chronically Infected With the Larval Echinococcus granulosus - Xu, Shiping; Guo, Yuxin; Luo, Tiancheng; Jiang, Pengfei; Yan, Ziyi; He, Yan; Fu, Linlin; Liu, Hua; Gao, Zixuan; Wang, Dingmin; Sun, Zhengxiu; Yang, Xiaoying; et al. (Frontiers in Veterinary Science, 2022)
Background: The larval Echinococcus granulosus (E. granulosus) has evolved immune subversive strategies to downregulate host immune responses, however, the underlying mechanism is still largely unknown. It previously reported that the parasite infection can expand the population of regulatory B cells in mice, thereby inhibiting the anti-infective immunity. This study further investigated the holistic transcriptomic profiles of total splenic B cells induced by the larval E. granulosus infection. Method: The infection model of larval E. granulosus was established by intraperitoneal inoculation with 2000 protoscolexes. The splenic B cells were isolated by Magnetic-Activated Cell Separation (MACS), and then performed RNA sequencing to screen the differentially expressed genes (DEGs) post infection. The qRT-PCR was used to verify the expression of selected DEGs. Gene Ontology (GO) analysis, Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis and Co-expression network analysis were utilized to predict the potential biological processes, pathways and interaction of these DEGs, respectively. Results: A total of 413 differentially expressed mRNAs were identified in infected B cells, including 303 up- and 110 down-regulated genes. Notably, most differentially expressed mRNA related with inflammation and chemotaxis were significantly upregulated after infection. In line with these changes, significant expression upregulations of mRNAs associated with fatty acid oxidation, lipid synthesis, lipolysis, lipid transport and cholesterol biosynthesis, were observed in infected B cells. Co-expression network analysis showed an intimate interaction between the genes of immune and metabolism. Conclusion: The present study shows that the larval E. granulosus infection induces metabolic reprogramming in B cells, which provides a novel clue for clarifying the immunoregulatory mechanism of B cells in parasitic infection.